Influence of functional polymorphisms in TNF-α, IL-8, and IL-10 cytokine genes on mRNA expression levels and risk of gastric cancer - Oliveira, Juliana Garcia de [UNESP]; Rossi, Ana Flávia Teixeira [UNESP]; Nizato, Daniela Manchini; Cadamuro, Aline Cristina Targa [UNESP]; Jorge, Yvana Cristina [UNESP]; Valsechi, Marina Curado [UNESP]; Venâncio, Larissa Paola Rodrigues [UNESP]; Rahal, Paula [UNESP]; Pavarino, Érika Cristina; Goloni-Bertollo, Eny Maria; Silva, Ana Elizabete [UNESP] (Springer Nature, 2015)
Functional polymorphisms in promoter regions can produce changes in the affinity of transcription factors, thus altering the messenger ribonucleic acid (mRNA) expression levels of inflammatory cytokines associated with the risk of cancer development. The goal of this study was to evaluate the influence that polymorphisms in the cytokine genes known as TNF-α-308 G/A (rs1800629), TNF-α-857 C/T (rs1799724), IL-8-251 T/A (rs4073), IL-8-845 T/C (rs2227532), and IL-10-592 C/A (rs1800872) have on changes to mRNA expression levels and on the risks of chronic gastritis (CG) and gastric cancer (GC). A sample of 723 individuals was genotyped using the polymerase chain reaction-restriction fragment length polymorphism (PCR-RFLP) technique. Relative mRNA expression levels were measured using quantitative real-time PCR (qPCR). Polymorphisms TNF-α-308 G/A and IL-8-251 A/T were not associated with risks of these gastric lesions. However, TNF-α-857 C/T, IL-8-845 T/C, and IL-10-592 C/A were found to be associated with a higher risk of GC, and IL-10-592 C/A was found to be associated with a higher risk of CG. The relative mRNA expression levels (RQ) of TNF-α, IL-8, and IL-10 were markedly downregulated in the CG group (median RQs = 0.128, 0.247, and 0.614, respectively), while the RQ levels of TNF-α in the GC group were upregulated (RQ = 2.749), but were basal for IL-8 (RQ = 1.053) and downregulated for IL-10 (RQ = 0.179). When the groups were stratified according to wild-type and polymorphic alleles, only for IL-8-845 T/C the polymorphic allele was found to influence the expression levels of this cytokine. IL-8-845 C allele carriers were significantly upregulated in both groups (GC and CG; RQ = 3.138 and 2.181, respectively) when compared to TT homozygotes (RQ = -0.407 and 0.165, respectively). In silico analysis in the IL-8 promoter region revealed that the presence of the variant C allele in position -845 is responsible for the presence of the binding sites for two transcription factors (REL and CREB1), which are involved in increased gene expression. Polymorphic alleles were not shown to have any effect on the expression levels of TNF-α and IL-10. Taken together, our findings provide evidence for an association of TNF-α-857 C/T, IL-8-845 T/C, and IL-10-592 C/A with a higher risk of gastric cancer and also demonstrate the influence that the polymorphic C allele of IL-8-845 has on changes to the gene expression levels of this cytokine.
Keywords: Chronic gastritis; Cytokines; Gastric cancer; Gene expression; Gene polymorphisms